2021
DOI: 10.1136/annrheumdis-2020-219137
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of nine monogenic autoinflammatory diseases reveals common and disease-specific correlations with allergy-associated features

Abstract: BackgroundMonogenic autoinflammatory diseases (AID) are caused by mutations in innate immune genes. The effects of these mutations on allergic inflammation are unknown.ObjectivesWe investigated allergic, immunological and clinical phenotypes in FMF (familial Mediterranean fever), CAPS (cryopyrin-associated periodic syndrome), TRAPS (tumour necrosis factor receptor-associated periodic syndrome), HIDS (hyper-IgD syndrome), PAPA (pyogenic arthritis, pyoderma gangrenosum and acne), DADA2 (deficiency of adenosine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Several studies have suggested that FMF protected against asthma and atopy, potentially due to protective linkage of MEFV with asthma associated genes like IL4RA (199)(200)(201). Although one study suggested that Turkish FMF patients may have elevated total serum IgE relative to healthy volunteers, this result was not seen in other cohorts, where there was a trend towards reduced serum IgE (199,201,202). Taken together, these results suggest that activation of the pyrin inflammasome attenuates human type 2 immune responses.…”
Section: Part 4: the Epidemiology Of Allergy In Autoinflammatory Dise...mentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have suggested that FMF protected against asthma and atopy, potentially due to protective linkage of MEFV with asthma associated genes like IL4RA (199)(200)(201). Although one study suggested that Turkish FMF patients may have elevated total serum IgE relative to healthy volunteers, this result was not seen in other cohorts, where there was a trend towards reduced serum IgE (199,201,202). Taken together, these results suggest that activation of the pyrin inflammasome attenuates human type 2 immune responses.…”
Section: Part 4: the Epidemiology Of Allergy In Autoinflammatory Dise...mentioning
confidence: 99%
“…One way to investigate the interaction between autoinflammatory pathways and type 2 immunity is to investigate the prevalence of allergic clinical and immunological phenotypes in subjects with monogenic autoinflammatory diseases ( Table 1 ). Because single gene mutations promote activation of discrete innate pathways, this approach can assess the in vivo roles of dysregulated autoinflammatory pathways in regulating human type 2 immune responses ( 199 ). This question has been most extensively studied in FMF, perhaps because it was the first autoinflammatory disease to be linked to a causative gene ( 16 ) ( Table 1 ).…”
Section: Part 4: the Epidemiology Of Allergy In Autoinflammatory Dise...mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, non-type 2 factors such as IgG1 immunocomplexes and complement activation system have also a role in both allergy and IgG4-RD ( 113 115 ) ( Table 1 ). For example, asthma and chronic rhinitis can be caused by neutrophil- driven inflammation ( 116 , 117 ), which may underlie the high prevalence of rhinosinusitis in patients with certain autoinflammatory diseases ( 118 , 119 ). Another example is the association of inflammasome activation with eczema ( 120 ).…”
Section: Type 2 Immunity Vs Allergy In Igg4-rdmentioning
confidence: 99%